FAMA's product brand: An analysis of product penetration strategy / Liyana Mohammad Zakaria - Mohammad Zakaria, Liyana (Faculty of Business and Management, 2008)
This research has been conducted in order to know about ‘ FAMA's Product Brand: An Analysis of Product Penetration Strategy ’. The dependent variable is product brand while the independent variables are promotion strategy, market development and product development. This research is conducted in Melaka area. In order to completing this research, 80 questionnaires have been distributed. The respondents are those FAMA's product brand user. In order to her the result from this research, the researcher has used SPSS program to analyze data from the information gathered. To analyze the data, researcher has used the reliability analysis, frequency distribution and descriptive static using the SPSS program. This study is basically undertaken to identify the effectiveness of FAMA's promotion strategy in enhancing FAMA's product brand. Through this objective, researcher has found that FAMA's have not actively promoting FAMA's product brand which are Agromas and oOemas. Besides, FAMA's also did not create an effective promotion strategy. In term of market development, most of respondent find that it is easy to find FAMA's product brand in the market but FAMA must be able to find other new market for example by export their product to other countries. Meanwhile, for product development, even though most respondent satisfied with the product quality of FAMA's product brand, FAMA must take an incentive to improve the quality of the product so that the product can compete with other product in the market.